Dziecko i jego rodzinny dom – na marginesie utworów wspomnieniowych XX-lecia międzywojennego - Kiełtyk-Zaborowska, Izabela (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
During the interwar period a number of novels describing family environment was written. An important element of those novels are memories as the childhood memories create and shape the character and influence the whole life. Universal topics described in the discussed novels was deepened with the kaleidoscope of presented values. The protagonists described in the novels, on the basis of their childhood memories, build their adult world. Coming back to a family house allows to analyze family relations. Love, support, safety, trust, help and understanding – these are the values which can be discovered in memories. Simultaneously, they are often average words without any value.
Keywords: childhood; family house; interwar literature; memories